150 years of teaching plant pathology at McGill University - Estey, Ralph (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2007)
In the 150 years between the time Sir William Dawson was lecturing on the diseases of fruit trees and vegetables, in 1856, and the plant pathology lectures given by Ajjamanda Kushalappa, in 2006, more than 29 members of the teaching staff at McGill University have given lectures that included significant amounts of plant pathology information. These were both men and women, at all academic levels, from lecturer to full professor, and on both campuses of McGill University. Their history shows that they have played a major role in Canadian plant pathology.